Talon Cusp Associates With MMP2 in a Cohort of Individuals Born With Oral Clefts. (May 2021) - Cavalcante, Bianca G. N.; Lacerda, Rosa Helena W.; Assis, Ionária O.; Bezamat, Mariana; Modesto, Adriana; Vieira, Alexandre R.
Objective: The aim of this study was to use dental development as a tool to subphenotype oral clefts and investigate the association of MMP2 with dentin-pulp complex anomalies, in order to identify dental anomalies that are a part of a "cleft syndrome." Design: Two hundred and ninety individuals born with cleft lip and palate were evaluated and several clinical features, such as cleft completeness or incompleteness, laterality, and presence of dental anomalies were used to assess each individual's cleft status. We tested for overrepresentation of MMP2 single nucleotide polymorphism rs9923304 alleles depending on individuals having certain dental anomalies. Chi-square and Fisher exact tests were used in all comparisons (α = .05). Results: All individuals studied had at least one dental anomaly outside the cleft area. Significant differences between individuals born with clefts with and without talon cusp ( P = .04) were observed for the frequency of the MMP2 less common allele. Conclusion: All individuals born with cleft lip and palate had alterations of the dentition, and a quarter to half of the individuals had alterations of the internal anatomy of their teeth, which further indicates that dental anomalies can be considered as an extended phenotype for clefts. MMP2 was associated with talon cusp in individuals born with oral clefts.